2012
DOI: 10.1002/app.36363
|View full text |Cite
|
Sign up to set email alerts
|

Highly refractive and organo‐soluble poly(amide imide)s based on 5,5′‐thiobis(2‐amino‐4‐methyl‐thiazole): Synthesis and characterization

Abstract: A new thioether-bridged diimide-diacid (DIDA) monomer was synthesized from the condensation of 5,5 0 -thiobis(2-amino-4-methyl-thiazole) (DA) and trimellitic anhydride at 1 : 2 molar ratio. A series of novel organic-soluble poly(amide imide)s (PAIs) bearing flexible thioether linkages and heteroaromatic thiazole groups were synthesized from DIDA with various commercially available aromatic diamines (1-5) via a direct polycondensation method with triphenyl phosphite and pyridine. The resulting polymers were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 53 publications
2
25
0
Order By: Relevance
“…In our previous works, an increase in solubility of polymers in low‐toxicity solvents was achieved by the introduction of flexible thioether linkages into the polymer backbones. In addition, recent studies demonstrated that bulky groups in the polymer backbone or as pendant groups can enhance the solubility and processability of aromatic PAs and PIs, without any significant reduction in thermal stability .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous works, an increase in solubility of polymers in low‐toxicity solvents was achieved by the introduction of flexible thioether linkages into the polymer backbones. In addition, recent studies demonstrated that bulky groups in the polymer backbone or as pendant groups can enhance the solubility and processability of aromatic PAs and PIs, without any significant reduction in thermal stability .…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, our research group has been developing structurally modified PAs and PIs with improved solubility and processability through the introduction of sulfur‐containing linkages (—S—, —SO— or —SO 2 —), non‐coplanar structures and bulky pendant groups into the polymer backbones . It was found that the incorporation of both hydrogen‐bonded amide groups and flexible thioether linkages resulted in poly(amide imide)s (PAIs) with enhanced solubility and processability . Aromatic PAIs possess desirable characteristics as they retain good mechanical properties at high temperatures when compared with aromatic PIs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the introduction of the sulfur atom is an effective way to prepare high refractive index polymers for its high molar refraction and low optical dispersity of refractive index. There have been many reports on sulfur‐containing optical polymers including epoxies, polyurethanes, polymethacrylates, polyarylenethioethers and polyimides . Among them, polyimides (PIs) are promising candidates for advanced optical applications.…”
Section: Introductionmentioning
confidence: 99%
“…25 This class of compounds is well known as a prodrug for the treatment of type-2 diabetes, 26 and aminothiazole-4-carboxylate derivatives are known as active compounds against Mycobacterium tuberculosis H37Rv and aketoacyl-ACP synthase mtFabH. 27 Aminothiazoles are also useful in the synthesis of polymers 28,29 and dyes. 30,31 Due to the multi-dimensional importance of aminothiazoles and their derivatives, several methods have been reported in the literature for their synthesis.…”
Section: Introductionmentioning
confidence: 99%